Manajemen diri untuk meningkatkan motivasi belajar pada remaja dengan conduct disorder - Anita Rohman (Universitas Muhammadiyah Malang, 2022)
Conduct disorder is a common and highly destructive psychiatric disorder that usually appears in childhood or adolescence and is characterized by severe antisocial and aggressive behavior. In this case, the subject often started physical fights, stole small items without facing a victim, often went out at night even though his parents prohibited him from starting before 13 years old, often skipped school starting before the age of 13 years, and behavioral disorders causing significant stress or dysfunction. clinical social aspect. Meanwhile, learning motivation is defined as a process in which goal-directed learning activities are initiated and maintained. Subjects have low learning motivation which is indicated by the absence of perseverance to do assignments, lack of interest in learning, lack of independence to do assignments, lack of appreciation in learning, and lack of confidence and pleasure in solving problems in lessons. The assessment methods used were interviews, observation, Wechsler Adult Intelligence Scale (WAIS), graphic tests (DAP, BAUM, HTP), Saks Sentence Completion Test (SSCT), and self reports. The intervention used is self management. The result of the intervention is that the subject has been able to improve the behavior of doing the task from 0 times to 3 times in one week. Subjects were also able to reduce the intensity and duration of excessive play behavior from 4 times a week with a duration of more than 6 hours per day, to 2 times a week with a duration of 2-4 hours per day.